Social Vulnerability and Mental Health Inequalities in the “Syndemic”: Call for Action - Mezzina, Roberto; Gopikumar, Vandana; Jenkins, John; Saraceno, Benedetto; Sashidharan, S. P. (Frontiers in Psychiatry, 2022)
Covid-19 is referred to as a ‘syndemic’, i.e. the consequences of the disease are exacerbated by social and economic disparity. Poor housing, unstable work conditions, caste, class, race and gender based inequities and low incomes have a profound effect on mental health and wellbeing. Such disparities are increasing between, among and within countries and are exacerbated by human rights violations, in institution and in society, stigma and discrimination. Social capital can mediate health outcomes, through trust and reciprocity, political participation, and by mental health service systems, which can be coercive or more open to demand of emancipation and freedom. Societal inequalities affect especially vulnerable groups, and Covid itself had a wider impact on the most socially vulnerable and marginalised populations, suffering for structural discrimination and violence. There are complex relations among these social processes and domains, and mental health inequalities and disparity. Participation and engagement of citizens and community organizations is now required in order to achieve a radical transformation in mental health. A Local and Global Action Plan has been launched recently, by a coalition of organizations representing people with lived experience of mental health care; who use services; family members, mental health professionals, policy makers and researchers, such as the International Mental Health Collaborating Network, the World Federation for Mental Health, the World Association for Psychosocial Rehabilitation, the Global Alliance of Mental Illness Advocacy Networks (GAMIAN), The Mental Health Resource Hub in Chennai, India and others. The Action Plan addresses the need for fundamental change by focusing on social determinants and achieving equity in mental health care. Equally the need for the politics of well-being has to be embedded in a system that places mental health within development and social justice paradigm, enhancing core human capabilities and contrasting discriminatory practices. These targets are for people and organizations to adopt locally within their communities and services, and also to indicate possible innovative solutions to Politics. This global endeavour may represent an alternative to the global mental discourse inspired by the traditional biomedical model.